Process Innovation and the Persistence of Monopoly with Labour-Managed Firms - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1997)
The issue of the persistence of monopoly when at least one labour-managed firm takes part in an auction for a cost-reducing innovation is tackled in this paper. It is shown that (i) when the incumbent is a profit-maximizing firm while the entrant is a labour-managed firm, monopoly persists; (ii) when both firms are labour-managed, monopoly persists only if the technology initially employed by the incumbent is highly inefficient as compared to the new one; and, finally, (iii) when the incumbent is labour-managed while the outsider is a profit seeking agent, then entry always occurs and monopoly changes hands.
Keywords: 330